2017
DOI: 10.1136/oemed-2016-103750
|View full text |Cite
|
Sign up to set email alerts
|

Hearing loss associated with repeated MRI acquisition procedure-related acoustic noise exposure: an occupational cohort study

Abstract: From our longitudinal cohort study, it appeared that exposure to noise from voluntarily MRI scans may have resulted in a slight amount of hearing loss. Mandatory use of hearing protection might have prevented more severe hearing loss. Lack of consistency in findings between the left and right ears and between the two exposure measures prohibits definitive conclusions. Further research that addresses the study's methodological limitations is warranted to corroborate our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…MR-volunteer-related noise exposure was managed with mandatory use of hearing protection devices. MR-volunteer-related acoustic noise exposure was associated with a small increase of hearing loss (Bongers et al, 2017) which implies the potential of an additional noise exposure for MR-volunteers despite the use of hearing protection. MR-volunteerrelated acoustic noise exposure may constitute an additional risk factor for developing hypertension, but given that we saw a protective effect for being a volunteer on the chance of developing hypertension this effect must have been minimal.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…MR-volunteer-related noise exposure was managed with mandatory use of hearing protection devices. MR-volunteer-related acoustic noise exposure was associated with a small increase of hearing loss (Bongers et al, 2017) which implies the potential of an additional noise exposure for MR-volunteers despite the use of hearing protection. MR-volunteerrelated acoustic noise exposure may constitute an additional risk factor for developing hypertension, but given that we saw a protective effect for being a volunteer on the chance of developing hypertension this effect must have been minimal.…”
Section: Discussionmentioning
confidence: 96%
“…Such MR-volunteer scans result not only in exposure to SMF, but also in exposure to motion induced TvMF, to pulsed time gradient magnetic fields (GMF) and radiofrequency fields (RF). The latter two exposure types are present during active scanning procedures together with exposure to acoustic noise (Bongers et al, 2017). Human and animal studies on cardiovascular effects of acute MRI-related EMF exposure have either shown no effect or indicated an effect within safety limits (Hartwig et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Projectile injury and subsequent morbidity and mortality from ferromagnetic objects being drawn into the bore of the MRI scanner have been well documented and reviewed (11). Hearing loss has also been associated with occupational exposure to MRI (12). Painful peripheral nerve stimulation is known to occur with rapid changes in field strength.…”
Section: Risks Of Mri With Medical Devicesmentioning
confidence: 99%
“…The disadvantages of the investigation are the long test time and high levels of noise exposure during imaging. 4 Although headphones and earplugs are used to reduce noise during MRI, patients are still exposed to very loud sounds. 5 It is accepted that the noise exposure during MRI does not have a negative effect on hearing functions.…”
Section: Introductionmentioning
confidence: 99%